2008
DOI: 10.1002/bin.256
|View full text |Cite
|
Sign up to set email alerts
|

Brief functional anlaysis and treatment of elopement in preschoolers with autism

Abstract: As a result of the impact of functional analysis methodologies in identifying maintaining variables of problem behavior, considerable research has been devoted to tailoring the methodologies to be practical for an outpatient setting. The purpose of this study was (a) to use brief functional analysis (BFA) methodologies to empirically demonstrate the function of elopement exhibited by two preschoolers diagnosed with autism and (b) to develop function-based interventions derived from the results of the BFA. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 7 publications
1
57
0
Order By: Relevance
“…Only 25% of subjects' elopement was maintained by escape from demands, and 10% was maintained by automatic reinforcement. Regardless of function, when a treatment was implemented, FCT was the most common intervention (Davis et al, 2013;Falcomata et al, 2010;Gibson et al, 2010;Lehardy et al, 2013;Perrin et al, 2008;Stevenson et al, 2015;Tarbox et al, 2003), followed by NCR (Kodak et al, 2004;Lang et al, 2010;Perrin et al, 2008;Tarbox et al, 2003) and DRO (Call et al, 2011). None of the articles in the current review reported interventions for elopement maintained by automatic reinforcement.…”
Section: Functional Analysis Results and Interventionmentioning
confidence: 90%
See 4 more Smart Citations
“…Only 25% of subjects' elopement was maintained by escape from demands, and 10% was maintained by automatic reinforcement. Regardless of function, when a treatment was implemented, FCT was the most common intervention (Davis et al, 2013;Falcomata et al, 2010;Gibson et al, 2010;Lehardy et al, 2013;Perrin et al, 2008;Stevenson et al, 2015;Tarbox et al, 2003), followed by NCR (Kodak et al, 2004;Lang et al, 2010;Perrin et al, 2008;Tarbox et al, 2003) and DRO (Call et al, 2011). None of the articles in the current review reported interventions for elopement maintained by automatic reinforcement.…”
Section: Functional Analysis Results and Interventionmentioning
confidence: 90%
“…Scorers disagreed on the type of FA in one article (Perrin, Perrin, Hill, & DiNovi, 2008). Authors of the article stated they used a "brief FA" (one scorer accordingly scored "brief FA"); however, their FA procedures were "multi-element" according to the definition utilized in this review (the other scorer accordingly scored "multi-element FA").…”
Section: Functional Analysis Results and Interventionmentioning
confidence: 97%
See 3 more Smart Citations